Plantar force characterization during rowing for top athletes - Gu, Y.; Li, J.; Lake, M. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. I, 2008)
Introduction: A biomechanical investigation into the efficiency of rowers is an im portant research field for enhancing the performances of the team. The rowing system comprised of three major components- the rowers, the shell and the oar. Most research has been solely concentrated on the force exerted between the hand and the oar [1, 2], while there is very limited understanding of the movement of the trunk and body segments, particularly the foot, during rowing, which is equally important. Detailed dynamical investigation of the movement of the foot (important restriction between rower and shell) during rowing will lead to improved understanding of the mechanics of rowing. This study aimed to characterize the biomechanics of a rowing process by examining the profile and timing of plantar forces produced during rowing between rowers. The results were compared to the deformation and force distribution of the feet during other sports with the aid of computationally modeling using high performance computing. Methods Tests were carried out in the professional training base at Qiandao Lake with eight female Chinese national rowers. An in-shoe force measurement system with 99 force sensors (Pedar System, Novel, Germany) connected to a data logging system was used to measure plantar forces during rowing. All sensors of the insole were individually calibrated before testing with the aid of the Trublu calibration device (Novel, Germany). To systematically map the load distribution on the foot during rowing, the plantar surface of each rower was divided into different anatomical regions. The peak force exerted on each region was normalized against the body weight of the rower. The time of peak force occurrence for each rower was normalized against the full loading cycle. Results The system has successfully determined the peak force and the force distribution over different regions. The forces on different anatomical regions were significantly different with the medial metatarsal heads, lateral metatarsal heads and great toe contributing to major proportions of the overall foot force during rowing. The pattern of force distribution between each region is comparable between rowers. Most rowers reach the peak plantar force nearly at the same time in one cycle, however, the gap between some rowers are still quite significant even in these eperienced athletes. This has to be considered in the team selection and training to enable the team to perform in a more coordinated pattern. Discussion / Conclusions This work systematically studied the plantar force characteristics during rowing for top athletes. Plantar force value was not particularly high in rowing than in other sports, as the athlete sit on the shell that bears the major body weight. Results showed that the peak force region is significantly different from other sports such as running and jumping, in which the high force is in the medial metatarsal heads and great toe regions. The results showed that lateral metatarsal heads area was under high pressure in rowing which indicate the muscle strength training for this part is of great significance. The different time required to reach the peak force for each individual rower within the team also highlighted the importance of these biomechanical studies in team selection or training to improve their overall performance.